Anthropogenic sources stimulate resonance of a natural rock bridge. Issue 18 (24th September 2016) - Moore, Jeffrey R.; Thorne, Michael S.; Koper, Keith D.; Wood, John R.; Goddard, Kyler; Burlacu, Relu; Doyle, Sarah; Stanfield, Erik; White, Benjamin
Abstract: The natural modes of vibration of bedrock landforms, as well as the sources and effects of stimulated resonance remain poorly understood. Here we show that seismic energy created by an induced earthquake and an artificial reservoir has spectral content coincident with the natural modes of vibration of a prominent rock bridge. We measured the resonant frequencies of Rainbow Bridge, Utah using data from two broadband seismometers placed on the span, and identified eight distinct vibrational modes between 1 and 6 Hz. A distant, induced earthquake produced local ground motion rich in 1 Hz energy, stimulating a 20 dB increase in measured power at the bridge's fundamental mode. Moreover, we establish that wave action on Lake Powell, an artificial reservoir, generates microseismic energy with peak power ~1 Hz, also exciting resonance of Rainbow Bridge. These anthropogenic sources represent relatively new energy input for the bridge with unknown consequences for structural fatigue. Key Points: We identify and describe eight resonant modes of Rainbow Bridge, Utah, between 1 and 6 Hz Lake Powell, like other lakes in Utah, generates seismic energy around 1 Hz from wave action The lake microseism and a distant induced earthquake stimulated low‐level resonance of the bridge